Atención de enfermería en complicaciones postparto en pacientes con riesgo obstétrico. una revisión bibliográfica - Caiza Tituaña, Verónica Cristina (2025)
Background: Obstetric risk considers not only the possibility of harm, but also the impact or consequences of an adverse event. This becomes important in the context of pregnancy, as catastrophic events, such as the death of a pregnant woman or newborn, are rare. However, the severity of these outcomes, the liability of providers, as well as the implications of loss for families in the long term, have focused ‘high - risk’ obstetric practice on prevention. Objective: To analyze the available scientific evidence on nursing intervention strategies for postpartum complications in obstetrically at - risk patients. Materials and Methods: A literature review was carried out, using databases such as PubMed, SciELO, Elsevier and LILACS. In addition, inclusion and exclusion criteria were applied, limiting the search to studies published between 2019 and 2024. Articles were analyzed under the PRISMA guidelines, and information was synthesized. Results: After applying the inclusion and exclusion criteria, 33 articles were included in the review. The most common postpartum complications identified were hemorrhage due to uterine atony, infections, thrombotic disorders and mental health problems such as postpartum depression. Interventions such as perineal massage and acupressure reduced pain and improved recovery. The need for specific protocols and ongoing training of nursing staff to optimize postpartum care could be established. Conclusion: Postpartum nursing care is crucial to reduce complications, especially in patients at obstetric risk. Specific interventions and the use of non - invasive technologies have been shown to be effective. However, better training and appropriate strategies that address both the physical and emotional health of mothers are required.